TAX COLLECTION AND ITS IMPLICATIONS FOR THE SOCIOECONOMIC DEVELOPMENT OF THE UCAYALI REGION - Viviano Sare, Kiara Angie (2026)
Objective: Determine the implication of tax collection on the socioeconomic development of the Ucayali region. Method: A quantitative, applied approach was chosen, with a non experimental design and a descriptive level of study, taking data from official sources such as SUNAT, BCRP and INEI. Results: We have that the tax collection in Ucayali showed a positive trend, rising from S/ 314 million in 2012 to S/ 966 million in 2022. Through the research, it was observed that the growth of tax collection did not maintain a proportional relationship with public investment nor with the sustained improvement of formal employment. Regarding the dimension of income and per capita expenditure, a slight recovery was observed following the COVID-19 pandemic. Discussion: Therefore, tax collection represents a relevant method to strengthen and improve the State’s financial capacity; however, its impact on economic and social development also depends on structural factors such as the efficiency of public spending, labor and commercial informality, institutional capacity, and productivity with various existing limitations. Conclusion: In summary, tax collection significantly influences the socioeconomic development of the Ucayali region. However, it does not occur immediately due to structural and institutional causes, limiting and preventing the expected socioeconomic development.